The future of work regional perspectives. (Metro Manila, Philippines Asian Development Bank, 2018)
Recent technological innovation in fields such as robotics, automation, and artificial intelligence have reduced the number of workers required in a range of sectors, while lowering costs and increasing reliability. This trend has led policy makers, academics, chief executive officers, and entrepreneurs to ask what types of jobs will be most affected, what new skillsets will be needed for the jobs of tomorrow, and how governments can ease the transition.This study identifies concrete policy actions countries in these regions could take to face up to the challenges and seize the opportunities presented by emergent technology. It is a copublication between African Development Bank, Asian Development Bank, European Bank for Reconstruction and Development, and Inter-American Development Bank.
Keywords: Social rights -- Developing countries; Health care reform -- Asia; Information and communications technology; Electronic books